Mercy Pregnancy and Emotional Well‐being Study (MPEWS): Understanding maternal mental health, fetal programming and child development. Study design and cohort profile. Issue 4 (25th January 2017) - Galbally, Megan; van IJzendoorn, Marinus; Permezel, Michael; Saffery, Richard; Lappas, Martha; Ryan, Joanne; van Rossum, Elisabeth; Johnson, Andrew R.; Teti, Douglas; Lewis, Andrew J.
Abstract: Maternal mental health represents a significant global health burden. The Mercy Pregnancy and Emotional Well‐being Study (MPEWS) was established to provide a comprehensive investigation of early developmental mechanisms and modifiers for maternal, fetal and child emotional well‐being. MPEWS is a prospective, longitudinal study from pregnancy to 36 months postpartum that includes diagnostic measures of maternal mental health, observational measures of the mother–infant relationship, measures of child development, and repeat biological sampling. A total of 282 pregnant women were recruited in early pregnancy from the Mercy Hospital for Women in Melbourne, Australia, including 52 women on antidepressant medication, 31 non‐medicated women meeting diagnostic criteria for current unipolar depression or dysthymia, and 65 women with a past history of depression. Sample recruitment characteristics included a mean age of 31 years and average gestation of 16 weeks. The MPEWS cohort was comparable to national averages for Australia on key pregnancy and birth variables. Those participants taking antidepressant medication had higher mean Edinburgh Postnatal Depression Scale (EPDS) and State Trait Anxiety Inventory (STAI) scores than the cohort as a whole but were comparable on other key variables. The MPEWS protocol provides a unique opportunity to evaluate the impact of pregnancy mental health on future maternal mental health and child development to aid the development of evidence‐based interventions. The study is open for collaborative proposals via approach to the principal investigators.